The Concept of Social Ethics in the Qur'an: A Thematic Tafsir Study of the Verses on Transactions - Ahmad Akbar Fauzi; Yeti Dahliana; Alfiyatul Azizah; Kharis Nugroho; Andri Nirwana AN (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The Qur'an, as a guide for human life, not only regulates the relationship between humans and Allah (habl min Allah), but also the relationship between humans with one another (habl min al-nas).Social ethics has become one of the important topics discussed in the verses of the Qur'an to create a harmonious social life, full of tolerance, and based on human values.This research aims to examine the concept of social ethics in the Qur'an in order to provide a comprehensive understanding for the community.The method in this research uses library research.The research results show that the Qur'an provides universal principles in social ethics that are relevant for all times and can be a solution to various social problems faced by modern society.Thus, this study is expected to contribute to the strengthening of social values based on the Qur'an amidst the dynamics of contemporary societal life.Thus, this study is expected to contribute to strengthening social values based on the Qur'an amidst the dynamics of contemporary community life.